Faktor-Faktor Yang Berpengaruh Terhadap Pengungkapan Islamic Social Reportingpada Perbankan Syari’ah Indonesia Periode 2011 – 2015 - Arry - Eksandy; M. Zulman Hakim (Universitas Kristen Maranatha, 2018)
This study aims to determine the effect of Firm Size, Profitability and Leverage on the Disclosure of Islamic Social Reporting (ISR). Firm size is measured by Logaritma Natural (Ln) Total Assets, Profitability is measured by Return on Assets (ROA), Leverage is measured by Debt to Assets Ratio (DAR) and Disclosure of Islamic Social Reporting (ISR) is measured by the ISR Index.The population in this study is all sharia banking in the form of Sharia Commercial Bank in Indonesia during the period 2011-2015. The total samples tested were 8 Sharia Commercial Bank selected by purposive sampling technique. This research analyzes ISR index through bank annual report by using content analysis method. Data analysis techniques use panel data regression with EViews 9.0 program.The results of this study indicate that Firm Size and Profitability affect the Disclosure of Islamic Social Reporting (ISR), Leverage doesn’t affect the Disclosure of Islamic Social Reporting (ISR). Keywords: Disclosure of Islamic Social Reporting (ISR), Firm Size, Profitability, Leverage